PENERAPAN PEMBELAJARAN KOOPERATIF JIGSAW BERBANTUAN SLIDE PRESENTATION MATERI JARINGAN HEWAN (Journal of Biology Education, 2012)
The purpose of this study was to examine the effectiveness of the influence of type of Jigsaw cooperative learning model-assisted slide presentation on the learning achievements of  structure and function of animal tissues in MA Nadlatul Ulama Demak. This study was a research experiment one-shot Case Study. Sample of this study was the class XI and XI IPA IPA 1 2, determined by random sampling techniques. The success indicator of this study was at least 75% of students indicated  scored ? 70 learning achievement. The results of this study showed  the completeness results of studying in class XI IPA 1 was 80% of students and for  class XI IPA 2 was 83.33% of the students. Based on these results it was  concluded that the Jigsaw cooperative learning model-assisted slide presentation of learning could be effectively applied to the materials structure and function of animal tissues at  MA Nahdlatul Ulama Demak. The suggestions  was made for teachers to apply the Jigsaw cooperative learning model assisted by slide presentation in delivering learning material structure and function of animal tissues. Tujuan dari penelitian ini adalah untuk meneliti efektivitas pengaruh model pembelajaran kooperatif tipe Jigsaw berbantuan media slide presentation terhadap hasil belajar siswa pada pembelajaran struktur dan fungsi jaringan hewan di MA Nahdlatul Ulama Demak. Penelitian ini merupakan penelitian pre-eksperimen yang dilaksanakan dengan metode The one-shot Case Study. Sampel dari penelitian ini adalah kelas XI IPA 1 dan XI IPA 2 yang diambil dengan teknik random sampling dari tiga kelas yang ada. Keberhasilan dari penelitian ini adalah sekurang-kurangnya 75% siswa memperoleh nilai hasil belajar ? 70. Hasil penelitian menunjukkan ketuntasan hasil belajar di kelas XI IPA 1 sebesar 80% siswa dan di kelas XI IPA 2 sebesar 83,33%  siswa. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa model pembelajaran kooperatif tipe Jigsaw berbantuan slide presentation efektif diterapkan pada pembelajaran materi struktur dan fungsi jaringan hewan di MA Nahdlatul Ulama Demak. Saran yang diajukan agar guru menerapkan model pembelajaran kooperatif tipe Jigsaw berbantuan slide presentation dalam menyampaikan pembelajaran materi struktur dan fungsi jaringan hewan.